O tempo e o clima : análise da dinâmica climática e das notícias veiculadas pelos meios de comunicação em Cuiabá, Mato Grosso - Araújo, Adilson Ribeiro de (2018)
This research intends to evaluate the content of the news related to climate change and the historical data series of temperature, rainfall and relative humidity of three conventional meteorological stations of. Monthly and annual averages of air temperature (maximum, minimum and compensated), monthly and annual precipitation totals were used, as well as a monthly and annual total relative humidity of the period from 1961 to 2016. For the analysis of the Cuiabá news media about weather, climate and special topics, the contents of the press with written and digital circulation were selected, distributed among the two main newspapers of the state: Gazeta Digital and Diário de Cuiabá. In the television media, two channels with the largest audience were selected, both for the capital and programming that encompasses the interior of the State: TV Centro América (Rede Globo) and TV Vila Real (Record TV). The focus of the research was based on the problematization about how the content is disseminated to readers and viewers. The results of the media convey the reports with alarmist content. Regarding the analysis of the reports disseminated by the Cuiabá media, a predominant content on anthropogenic global warming was observed for the reader and viewer from Mato Grosso. The data that were analyzed involve 9,096 reports between 2005 and 2015 of the respective media already mentioned. The research highlights the reports of the Intergovernmental Panel on Climate Change, analyzes the content of the speeches, with regional reach, and the effects of media information and the connection to society on climate change. A significant number of news related to the climate in the main regional media in the state of Mato Grosso was found. However, the majority refers to time rather than climate. From the climatic dynamics of the historical series analyzed, it can be concluded that the results obtained from the variables of temperature, rainfall and air humidity presented distinct periods, with climatic cycles, a small abnormality in the values represented quantitatively of the data. However, it was observed that the seasons have two well defined periods, one rainy from November to March and another dry season from May to October. With average temperature indexes of 26.2º, the average minimum was 21.5º C and the average maximum was 32.5º C. The average percentage of air humidity was 70.9%, in the months of June to October, this percentage shows a significant drop in the dry season. The average rainfall was 1,243.13 mm. Finally, it is noted that climate change data are relatively lower compared to the IPCC global warming perspective, where it relates these changes to the impacts of society on the planet. Thus, in the results, there is a tendency towards natural variability rather than global warming, as the media has predicted, when comparing the convergence and divergence of the media discourse.